Corporate Governance Terhadap Kinerja Maqashid Syariah Dengan Intellectual Capital Sebagai Variabel Mediasi - Diky Satria; Mismiwati Mismiwati; Lidia Desiana; Siti Juairiah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2021)
This study aims to analyze and determine the effect of corporate governance on the performance of sharia maqhasid with intellectual capital as a mediating variable in Islamic Commercial Banks in Indonesia for the 2014-2018 period. The population in this study are Islamic Commercial Banks in Indonesia for the 2014-2018 period. The technique used is the annual report for the 2014-2018 period on 8 Islamic Commercial Banks. The type of data used is secondary data. The data analysis technique in this study used SPSS 21 software, which consists of descriptive statistical analysis, classical assumption test, multiple regression analysis, and mediation testing using the causal step and sobel test methods. By using multiple regression analysis, the results of this study indicate that corporate governance has a negative and significant effect on intellectual capital. Corporate governance does not affect the performance of sharia maqhasid. Intellectual capital has a negative and significant effect on the performance of sharia maqhasid. Then based on the results of the analysis using the casual step and sobel test method, intellectual capital mediates the effect of corporate governance on the performance of sharia maqhasid.